Culture And Community Partnership Approach to Making a Healthy Indonesian Society (GERMAS) With The Helix Method - Angga Irawan; Ahmad Hidayat; Jami Hariyadi (University of Muhammadiyah Semarang, 2020)
GERMAS is a movement with the aim of improving people's healthy life and leaving unhealthy habits and behavior of society. One of the areas that become national priorities based on the Decree of the Minister of Villages for Disadvantaged Areas and Trans-Migration of the Republic of Indonesia Number 126 of 2017 concerning the determination of priority villages for village development targets, development of underdeveloped areas and transmigration, including the Village Assistance of Banjar Regency, South Kalimantan Problems in the health sector in Banjar Regency can be seen from the Health Profile Data for Banjar Regency in 2017 which shows the incidence of infectious and non-communicable diseases that are still experienced by many people in Banjar Regency such as ISPA, Hypertension, Rheumatism, Gastritis, Duodenitis, Diarrhea, Dermatitis and Pulmonary TB. One of the concepts that can be used in the implementation of the GERMAS action program is the concept of a partnership with an approach to religious figures, educational institutions, society, and the media. This study uses a quantitative descriptive-analytical design with a quantitative descriptive survey method with a random sampling technique. By using the instrument used in this study is a questionnaire sheet. Based on the research results obtained as follows: knowledge level as much as 53%, physical activity 70%, eating fruit and vegetable foods 75%, alcohol consumption 56%, health checks 15%, environmental hygiene 45%, using a latrine 23%, use of media as much as 80% and social activities as much as 80%. The results of this study hope that the people of Desa Pembantanan will implement a community movement for healthy living which includes 4 indicators, namely increasing knowledge, not drinking alcohol, environmental hygiene, and not using latrines, so that they can avoid health problems from non-communicable diseases.